Risk management committee and disclosure of hedging activities information among Malaysian listed companies - Abdullah, Azrul; Ku Ismail, Ku Nor Izah; Mat Isa, Norshamshina (American Scientific Publishers, 2015)
This paper examines the relationship between Risk Management Committee (RMC) characteristics and the extent of hedging activities disclosure within the annual reports of the Malaysian listed companies.In particular, relationships are tested on RMC size, independence, RMC meeting, RMC gender diversity and RMC training.Our regression analysis shows that RMC independence significantly and negatively influences the extent of hedging activities information disclosure, while RMC meeting positively influences the disclosure.The implications of these findings are discussed.